Hemodynamics and cardiac autonomic modulation after an acute concurrent exercise circuit in older individuals with pre- to established hypertension (Clinics, 2021)
OBJECTIVES: Few studies have investigated whether post-exercise hypotension (PEH) after concurrent exercise (CEX) is related to changes in cardiac output (Q) and systemic vascular resistance (SVR) in older individuals. We tested whether PEH after a single bout of CEX circuits performed in open-access facilities at the Third Age Academies (TAA) in Rio de Janeiro City (Brazil) would be concomitant with decreased Q and SVR in individuals aged X60 years with prehypertension. Moreover, we assessed autonomic modulation as a potential mechanism underlying PEH. METHODS: Fourteen individuals (age, 65.8±0.9 y; systolic/diastolic blood pressure [SBP/DBP], 132.4±12.1/72.8± 10.8 mmHg; with half of the patients taking antihypertensive medications) had their blood pressure (BP), heart rate (HR), Q, SVR, HR variability (HRV), and spontaneous baroreflex sensitivity (BRS) recorded before and 50 min after CEX (40-min circuit, including seven stations of alternate aerobic/resistance exercises at 60–70% HR reserve) and non-exercise control (CONT) sessions. The study protocol was registered in a World Health Organization-accredited office (Trial registration RBR-7BWVPJ). RESULTS: SBP (D= 14.2±13.1 mmHg, p=0.0001), DBP (D= 5.2±8.2 mmHg, p= 0.04), Q (D= 2.2±1.5 L/min, p=0.0001), and BRS (D= 3.5±2.6 ms/mmHg; p=0.05) decreased after CEX as compared with the CONT session. By contrast, the HR increased (D=9.4±7.2 bpm, po0.0001), and SVR remained stable throughout the postexercise period as compared with the CONT session (D=0.10±0.22 AU, p=0.14). We found no significant difference between the CEX and CONT with respect to the HRV indexes reflecting autonomic modulation. CONCLUSION: CEX induced PEH in the older individuals with prehypertension status. At least in the first 50 min, PEH occurred parallel to the decreased Q and increased HR, while SVR was not different. The changes in autonomic outflow appeared to be unrelated to the acute cardiac and hemodynamic responses.